Ro’sumaliyah Vs Scarcity:: (Paradigma Pelemahan Terhadap Perekonomian Syari’ah) - Ulum, Miftachul (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2017)
Ro'sumaliyah (capitalism) is already so entrenched in the joints of causing weakening on human nature as creatures of Allah SWT. Scarcity itself occurred because of the use of excessive requirements and does not heed the concept of really is. Islam ensures that as long as humans live as human nature live in the world, the scarcity is not going to happen. One is to have exploited human nature as human beings so that they appear scarcity.